Harmonic Trace

Algebra Level 5

For any positive integer n n , the n × n n \times n matrix B ( n ) B(n) has components B ( n ) u v = H min ( u , v ) 1 u , v n B(n)_{uv} \; = \; H_{\min(u,v)} \hspace{2cm} 1 \le u,v \le n where H m H_m is the m t h m^\mathrm{th} Harmonic number: H m = j = 1 m 1 j m N . H_m \; = \; \sum_{j=1}^m \frac{1}{j} \hspace{2cm} m \in \mathbb{N}\;. If we calculate the trace T r [ B ( n ) 1 ] \mathrm{Tr}\big[B(n)^{-1}\big] of the inverse of the matrix B ( n ) B(n) , then it can be shown that n = 1 1 4 T r [ B ( n ) 1 ] + 5 = 1 A π B C \sum_{n=1}^\infty \frac{1}{4\,\mathrm{Tr}\big[B(n)^{-1}\big] + 5} \; = \; \frac{1}{A}\pi^B - C where A , B , C A,B,C are positive integers. Find the value of A + B + C A + B + C .

Inspiration 1

Inspiration 2


The answer is 11.

This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try refreshing the page, (b) enabling javascript if it is disabled on your browser and, finally, (c) loading the non-javascript version of this page . We're sorry about the hassle.

1 solution

Mark Hennings
Jun 23, 2020

We note that ( 0 B ( n ) 1 0 0 0 0 0 ( n + 1 ) n + 1 ) B ( n + 1 ) = ( 0 B ( n ) 1 0 0 0 0 0 ( n + 1 ) n + 1 ) ( H 1 H 2 B ( n ) H n 1 H n H 1 H 2 H n 1 H n H n + 1 ) = ( 0 I n 0 1 0 0 0 0 1 ) \begin{aligned} \left(\begin{array}{ccccc|c} & & & & & 0 \\ & & & & & \vdots \\ & & B(n)^{-1} & & & \vdots \\ & & & & & 0 \\ & & & & & 0 \\\hline 0 & 0 & \cdots & 0 & -(n+1) & n+1 \end{array}\right) B(n+1) & = \; \left(\begin{array}{ccccc|c} & & & & & 0 \\ & & & & & \vdots \\ & & B(n)^{-1} & & & \vdots \\ & & & & & 0 \\ & & & & & 0 \\\hline 0 & 0 & \cdots & 0 & -(n+1) & n+1 \end{array}\right) \left(\begin{array}{ccccc|c} & & & & & H_1 \\ & & & & & H_2 \\ & & B(n) & & & \vdots \\ & & & & & H_{n-1} \\ & & & & & H_n \\\hline H_1 & H_2 & \cdots & H_{n-1} & H_n & H_{n+1} \end{array}\right) \\[4ex] & = \; \left(\begin{array}{ccccc|c} & & & & & 0 \\ & & & & & \vdots \\ & & I_n & & & \vdots \\ & & & & & 0 \\ & & & & & 1 \\\hline 0 & 0 & \cdots & 0 & 0 & 1 \end{array}\right) \end{aligned} and hence B ( n + 1 ) 1 = ( 0 I n 0 1 0 0 0 0 1 ) ( 0 B ( n ) 1 0 0 0 0 0 ( n + 1 ) n + 1 ) = ( 0 B ( n ) 1 + ( n + 1 ) K ( n ) 0 ( n + 1 ) 0 0 0 ( n + 1 ) n + 1 ) \begin{aligned} B(n+1)^{-1} & = \; \left(\begin{array}{ccccc|c} & & & & & 0 \\ & & & & & \vdots \\ & & I_n & & & \vdots \\ & & & & & 0 \\ & & & & & -1 \\\hline 0 & 0 & \cdots & 0 & 0 & 1 \end{array}\right) \left(\begin{array}{ccccc|c} & & & & & 0 \\ & & & & & \vdots \\ & & B(n)^{-1} & & & \vdots \\ & & & & & 0 \\ & & & & & 0 \\\hline 0 & 0 & \cdots & 0 & -(n+1) & n+1 \end{array}\right) \\[4ex] & = \; \left(\begin{array}{ccccc|c} & & & & & 0 \\ & & & & & \vdots \\ & & B(n)^{-1} + (n+1)K(n) & & & \vdots \\ & & & & & 0 \\ & & & & & -(n+1) \\\hline 0 & 0 & \cdots & 0 & -(n+1) & n+1 \end{array}\right) \end{aligned} where K ( n ) K(n) is the n × n n \times n matrix all of whose components are 0 0 , except for 1 1 in the bottom-right corner. Thus T r [ B ( n + 1 ) 1 ] = T r [ B ( n ) 1 + ( n + 1 ) K ( n ) ] + n + 1 = T r [ B ( n ) 1 ] + 2 ( n + 1 ) \mathrm{Tr}\big[B(n+1)^{-1}\big] \; = \; \mathrm{Tr}\big[B(n)^{-1} +(n+1)K(n)\big] + n + 1 \; = \; \mathrm{Tr}\big[B(n)^{-1}\big] + 2(n+1) and hence we deduce that T r [ B ( n ) 1 ] = 1 + 2 r = 1 n 1 ( r + 1 ) = n 2 + n 1 n N \mathrm{Tr}\big[B(n)^{-1}\big] \; = \; 1 + 2\sum_{r=1}^{n-1}(r+1) \; = \; n^2 + n - 1 \hspace{2cm} n \in \mathbb{N} so that n = 1 1 4 T r [ B ( n ) 1 ] + 5 = n = 1 1 ( 2 n + 1 ) 2 = 1 8 π 2 1 \sum_{n=1}^\infty \frac{1}{4\,\mathrm{Tr}\big[B(n)^{-1}\big] + 5} \; = \; \sum_{n=1}^\infty \frac{1}{(2n+1)^2} \; = \; \tfrac18\pi^2 - 1 making the answer 8 + 2 + 1 = 11 8 + 2 + 1 = \boxed{11} .

0 pending reports

×

Problem Loading...

Note Loading...

Set Loading...